FUNCTIONAL TYPES OF UNCONNECTED COMPLEX SENTENCES OF HOMOGENEOUS COMPOSITION IN KARAKALPAK LANGUAGE BY THEIR LOCATION IN THE TEXT - Khalmuratov, Tajetdin Jumashevich (SCIENCE and SOCIETY, 2026)
The article is devoted to the consideration of functional types of unmarked compound sentences of homogeneous composition in the Karakalpak language in the text.
Keywords: complex sentences without conjunctions; Karakalpak language; conditions for the functioning of complex sentences without conjunctions in the text